Uji Aktivitas Antibakteri pada Ekstrak Etanolik Teripang Kering dari Ujung Pangkah Gresik - M. Ainul Mahbubillah; Putri Ayu Ika Setiyowati; Muhammad Badrut Tamam; Fika Nur Fitriana Putri Bukhori (Program Studi Pendidikan Biologi, 2022)
Sea cucumber is a potential fishery sub-sector, but its use still not popular because of its unfavorable physical form. However, from its unfavorable form, sea cucumbers contain many benefits as nutrition and medicine, including the presence of antimicrobial activity. The use of sea cucumbers as a nutrient is used by the people of Ujung Pangkah Gresik village as crackers. This study aims to prove the antimicrobial potential of dried sea cucumbers with crackers from Ujung Pangkah village, Gresik. The sea cucumbers have been boiled first before drying in the sun. The dried sea cucumbers were blended and then extracted using 96% ethanol. The extract was then sterilized by filtration using a 0.2 m PTFE filter. Extracts were tested using the Kirby-Bauer method on Mueller-Hinton Agar medium inoculated with Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhimurium, Burkholderia cepacia, and yeast Candida albicans. The control antibiotic tetracycline 30 µg/ml and antifungal 2,5 µg/ml fluconazole were used as comparisons. The results of this study showed that all ethanolic extracts of dry sea cucumber with concentrations of 5%, 10%, and 15% did not show any clear zone. While the clear zone was shown in the control of tetracycline and fluconazole. This was caused by the loss of antimicrobial activity in the ethanolic extract of dried sea cucumbers derived from antimicrobial peptides which were damaged by heating during boiling process.